ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS IX MTS PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL BERDASARKAN GENDER - Siti Rodiah (Jurnal Kajian Pembelajaran Matematika, 2019)
This research is a qualitative descriptive study to describe the mathematical reasoning abilities of class IX students in one of the MTs in Cimahi City City on the material of linaer equation system of two-variables. The purpose of this study was to analyze mathematical reasoning abilities based on gender and distribution, as well as profiles of students' mathematical reasoning abilities based on each indicator. The subjects of this study were 24 students consisting of 12 males and 12 females. Mathematical reasoning abilities are classified into 3 categories, namely low, medium, and high. The instrument used is 4 description questions that represent each indicator. This study produced data that explained that the average achievement of mathematical reasoning of female students was 62.0% (medium) with a distribution of 25% of low ability, 50% of medium ability, and 25% of high ability. Slightly lower, the average data on achieving male students' mathematical reasoning is 55.2% (medium) with a distribution of 50% with low ability and 50% with medium ability. Overall, the research data explains that the achievement of mathematical reasoning of class IX students is 58.6% (medium) with a distribution of 37.5% with low ability, 50% with medium ability, and 12.5% with high ability. Profiles based on indicators, grade IX students have high scores for indicators making analogies and providing explanations with models and low scores for indicators using patterns to analyze mathematical situations and draw conclusions.